Christianity and the African imagination: essays in honour of Adrian Hastings - Maxwell, David; Lawrie, Ingrid (Brill, 2002)
During the twentieth-century, Christendom shifted its centre of gravity to the Southern Hemisphere, Africa becoming the most significant area of church growth. This volume explores Christianity’s advance across the continent, and its capturing of the African imagination. From the medieval Catholic Kingdom of Kongo to a transnational Pentecostal movement in post-colonial Zimbabwe, the chapters explore how African agents – priests and prophets, martyrs and missionaries, evangelists and catechists – have seized Christianity and made it theirs. Emphasizing popular religion, the book shows how the Christian ideas and texts, practices and symbols, which have been adapted by Africans, help them accept existential passions and empower them through faith to deal with material concerns for health and wealth, and to overcome evil.
paid
Keywords: Africa; Christianity; Spirituality